Survival-Related lncRNA Landscape Analysis Identifies LINC01614 as an Oncogenic lncRNA in Gastric Cancer - Wu, Huijie; Zhou, Jingyuan; Chen, Songda; Zhu, Lingyu; Jiang, Mengjie; Liu, Aiqun (Frontiers in Genetics, 2021)
Background: Long non-coding RNAs (lncRNAs) reportedly play important roles in biomarker and tumorigenesis of gastric cancer (GC). This study aimed to determine the potential application of prognostic lncRNA signature and identified the role of LINC01614 in carcinogenesis in GC. Material and Methods: Data accessed from the Cancer Genome Atlas database was used to construct a lncRNA signature. Joint effect analysis of the signature and clinical parameters was performed to verify the clinical value of the signature. Co-expression analysis was conducted for prognostic lncRNAs and protein-coding genes. Moreover, the relative expression of LINC01614 was validated in GC tissues and cell lines. In vitro and in vivo experiments were conducted to analyze the biological functions of the newly identified gene in GC cells. Results: A seven-lncRNA (LINC01614, LINC01537, LINC01210, OVAAL, LINC01446, CYMP-AS1, and SCAT8) signature was identified as a promising prognostic signature in GC. Results indicated that the seven-lncRNA was involved in tumorigenesis and progression pathways. LINC01614 expression was identified and found to be upregulated in GC tissues and cells. The study findings revealed that LINC01614 promoted cell proliferation, migration, invasion, and epithelial-mesenchymal transition. Knockdown of LINC01614 arrested cell cycle distribution at the G2/M phase. Further, LINC01614 also promoted tumor growth in vivo. Conclusion: We developed an independent seven-lncRNA biomarker for prognostic prediction and identified LINC01614 as an oncogenic lncRNA in GC.